The effects of cold exposure on body composition: Analysis with Computerized Bioimpedance: Effects of cold exposure on body composition verified by computerized bioimpedance - Alvaro Brandão Lopes-Martins, Rodrigo; Vicente Barbosa, Ludymilla; Martins Barbosa Souza, Mirian; Beatriz Lobo, Anna; Assis Ribeiro Junior, Sebastião; Souza de Sá Filho, Alberto; Sardinha Leonardo , Patrícia (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Introduction: Weight gain and obesity are common concerns for midlife women. Obesity is characterized by an accumulation of body fat resulting in body weight at least 20% above the optimum. Objective: To evaluate the efficacy of cryolipolysis on body composition in midlife women. Methods: Thirty women aged 30-55 with overweight underwent three cryolipolysis sessions, (45 minutes each), spaced 15 days apart. Body composition was assessed using bioelectrical impedance before and after the intervention. Parameters measured included fat mass, lean mass, muscle mass, muscle/fat ratio, and total body water (TBW) percentage. Results: Significant reductions were observed in both absolute fat mass (from 26 ± 1.5 kg to 24.4 ± 1.51 kg, p<0.05) and fat mass percentage (from 34.4 ± 1.2% to 32.8 ± 1%, p<0.05). Lean mass remained stable (48.91 ± 1.56 kg to 48.82 ± 1.4 kg), with a significant increase in lean mass percentage (65 ± 1.2% to 67 ± 1.2%, p<0.05). Muscle mass percentage rise from 29 ± 0.6% to 31 ± 0.7% (p<0.05). The muscle/fat ratio improved significantly from 0.85 ± 0.04 to 0.95 ± 0.2 (p<0.05), and TBW percentage increased from 46.5 ± 0.9% to 48 ± 0.9% (p<0.01). Conclusion: Cryolipolysis significantly enhances body composition by reducing fat mass, maintaining lean mass, and improving muscle/fat ratio and hydration status. These findings underscore cryolipolysis as an effective non-invasive alternative for body contouring with potential health benefits, including improved metabolic and cardiovascular health. Future research should explore long-term effects and mechanisms to optimize clinical applications.